South-South trade: Some recent trends - Thomas Straubhaar (Intereconomics, 1986)
Increased trade among the developing countries is often seen as a viable and more gainful alternative to their trade with developed countries. The following article examines trends in the volume, composition and direction of South-South trade since 1970 and addresses the question as to whether the many existing barriers to South-South trade have in fact led to a bias against it.
Keywords: 330; International Trade